Selective Theta-Synchronization of Choice-Relevant Information Subserves Goal-Directed Behavior - Womelsdorf, Thilo; Vinck, Martin; Leung, Stan L.; Everling, Stefan (Frontiers in Human Neuroscience, 2010)
Theta activity reflects a state of rhythmic modulation of excitability at the level of single neuron membranes, within local neuronal groups and between distant nodes of a neuronal network. A wealth of evidence has shown that during theta states distant neuronal groups synchronize, forming networks of spatially confined neuronal clusters at specific time periods during task performance. Here, we show that a functional commonality of networks engaging in theta rhythmic states is that they emerge around decision points, reflecting rhythmic synchronization of choice-relevant information. Decision points characterize a point in time shortly before a subject chooses to select one action over another, i.e. when automatic behavior is terminated and the organism reactivates multiple sources of information to evaluate the evidence for available choices. As such, decision processes require the coordinated retrieval of choice-relevant information including (i) the retrieval of stimulus evaluations (stim.-reward associations) and reward expectancies about future outcomes, (ii) the retrieval of past and prospective memories (e.g. stim.-stim. associations), (iii) the reactivation of contextual task rule representations (e.g. stim.-response mappings), along with (iv) an ongoing assessment of sensory evidence. An increasing number of studies reveal that retrieval of these multiple types of information proceeds within few theta cycles through synchronized spiking activity across limbic, striatal and cortical processing nodes. The outlined evidence suggests that evolving spatially and temporally specific theta synchronization could serve as the critical correlate underlying the selection of a choice during goal-directed behavior.